2005
DOI: 10.1352/0895-8017(2005)110<145:ptreov>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Relative Efficacy of Verbal, Pictorial, and Tangible Stimuli for Assessing Preferences of Leisure Activities

Abstract: We measured the relationships between choice stimulus modalities and three basic discriminations (visual, visual matching-to-sample, and auditory-visual) using the Assessment of Basic Learning Abilities test. Participants were 9 adults who had moderate to profound developmental disabilities. Their most and least preferred leisure activities, identified by prior preference assessments, were presented using choice stimuli in three modalities (tangibles, pictures, and verbal descriptions) in an alternating-treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…For persons who have passed up to level 6, they selected their preferred stimuli consistently in all three modalities. These findings have been replicated with food (Conyers et al 2002;Schwartzman et al 2004), non-food items (Conyers et al 2002), leisure activities (de Vries et al 2005), and with work tasks (Reyer & Sturmey 2005).…”
Section: Research Findings Of the Ablamentioning
confidence: 85%
See 1 more Smart Citation
“…For persons who have passed up to level 6, they selected their preferred stimuli consistently in all three modalities. These findings have been replicated with food (Conyers et al 2002;Schwartzman et al 2004), non-food items (Conyers et al 2002), leisure activities (de Vries et al 2005), and with work tasks (Reyer & Sturmey 2005).…”
Section: Research Findings Of the Ablamentioning
confidence: 85%
“…2004), non‐food items (Conyers et al. 2002), leisure activities (de Vries et al. 2005), and with work tasks (Reyer & Sturmey 2005).…”
Section: Research Findings Of the Ablamentioning
confidence: 99%
“…These authors did note that participants had limited verbal communication abilities, and there were no formal assessments of participants’ skill levels before the comparison was conducted. Researchers then began to investigate the role of hypothesized prerequisite skills such as IQ (e.g., Cohen‐Almeida, Graff, & Ahearn, ; Wilder, Ellsworth, White, & Schock, ), matching abilities (e.g., Clevenger & Graff, ; Cohen‐Almeida et al, ; Graff & Gibson, ), verbal repertoires (e.g., Higbee, Carr, & Harrison, ; Kuhn, DeLeon, Terlonge, & Goysovich, ), and discrimination abilities (e.g., Conyers et al, ; de Vries et al, ). Overall, multiple prerequisite skills have been assessed across numerous investigations; however, it is difficult to draw conclusions on which skills are pertinent because they have not been assessed systematically.…”
mentioning
confidence: 99%
“…In addition to evaluating the effectiveness of how stimuli are presented during preference assessments, another area of research has focused on examining the modality of presenting stimuli during preference assessments. Studies have evaluated the effectiveness of using pictorial, vocal, and tangible modes of presentation in identifying preferences in individuals with SPMD (Conyers et al, 2002;Graff & Gibson, 2003;Higbee et al, 1999;Lee et al, 2008;Vries et al, 2005). For instance, Graff and Gibson (2003) used a paired-stimulus preference assessment procedure to compare if a tangible mode or a pictorial mode of presentation was more effective in identifying hierarchies of preferences between items.…”
Section: During Preference Assessmentsmentioning
confidence: 99%
“…Although most preference assessment procedures conducted with individuals with SPMD have used stimuli in object form (DeLeon & Iwata, 1996;Fisher et al, 1992;Pace et al, 1985;Roane et al, 1998;Wacker et al, 1985;Windsor et al, 1994), studies have demonstrated the utility of using pictorial and auditory modalities of presentation (Conyers et al, 2002;Graff & Gibson 2003;Higbee et al, 1999;Lee et al, 2008;Vries et al, 2005). One of the advantages of using a pictorial presentation is that sampling options that cannot be presented in an object form could be presented via the use of pictures (e.g., outdoor activities, community-based activities).…”
Section: Summary Of Guidelines For Practicementioning
confidence: 99%